Is there a relationship between fasting blood glucose levels and the incidence of polyhydramnios in pregnant women with gestational diabetes? : A Systematic Review - Rizky Febriansyah; Bangar Parlinggoman Tua; Mutia Juliana; Aditya Rifandi Zaenudin (The Indonesian Journal of General Medicine, 2026)
Introduction: Gestational diabetes mellitus (GDM) is associated with various adverse pregnancy outcomes, including polyhydramnios. However, the direct relationship between fasting blood glucose levels and the incidence of polyhydramnios in GDM populations remains debated. This systematic review aimed to evaluate the association between fasting glucose levels and polyhydramnios occurrence in pregnant women with GDM. Methods: A systematic review of observational studies examining the relationship between glucose parameters and polyhydramnios in GDM pregnancies was conducted. Thirty-five studies published to 2026 were identified,. Data extraction focused on study characteristics, GDM populations, glucose measurements, polyhydramnios occurrence, and statistical associations. Results: Polyhydramnios rates among GDM women ranged from 8.3% to 56.8%. Direct evidence from Dashe et al. and Xu et al. demonstrated significant positive correlations between amniotic fluid glucose concentration and amniotic fluid index (AFI) in diabetic populations (r=0.32, p=0.04; r=0.330, p=0.002). Xu et al. further showed strong correlation between amniotic fluid glucose and maternal fasting glucose (r=0.589, p<0.01). Critically, well-controlled GDM demonstrated significantly lower AFI (13.9±4.2 cm) compared to uncontrolled GDM (16.4±4.4 cm, p<0.05). Bartha et al. showed early GDM screening reduced hydramnios rates from 12.7% to 2.1% (p<0.0001). Late-onset GDM was identified in 4.8-11.8% of women with third-trimester polyhydramnios and prior negative screening. Discussion: The evidence supports an osmotic mechanism whereby maternal hyperglycemia leads to elevated amniotic fluid glucose, increasing amniotic fluid volume. The glucose-polyhydramnios relationship is modifiable through glycemic control, explaining apparent contradictions between studies. Studies failing to detect associations typically examined narrow glycemic ranges in normoglycemic populations. Conclusion: Fasting blood glucose levels are positively associated with polyhydramnios in GDM, mediated through amniotic fluid glucose concentration. Early detection and strict glycemic control significantly reduce polyhydramnios incidence and severity.